Antisociality and the Construct of Psychopathy: Data From Across the Globe. Issue 6 (18th October 2014) - Neumann, Craig S.; Hare, Robert D.; Pardini, Dustin A.
Abstract: Previous theory and research on the structural, longitudinal, and genetic nature of psychopathy have provided strong conceptual and empirical evidence that overt antisociality is a component of the psychopathy construct (Hare & Neumann, 2008, 2010; Lynam & Miller, 2012). However, determination of the strength of the association between antisociality and other psychopathic features has not been explored systematically. The current article draws on previously published large North American studies, as well as data from across the globe, to estimate the strength and pattern of the associations between overt antisociality and other psychopathic domains in a diverse set of samples. Structural equation modeling was used to estimate model parameters from samples that had data on either the Psychopathy Checklist‐Instruments (PCL‐R, PCL: YV, PCL: SV) or self‐report assessments that have known latent structures (SRP, B‐Scan 360). In addition, two relatively large samples (male offenders and young adult males), assessed with both the PCL‐R and the SRP, provided an opportunity to examine the link between antisociality and the other psychopathy domains across different assessment methods. The overall findings indicate that the associations were moderate to strong, depending on the nature of the sample, and clearly indicate that antisociality is a core component of the psychopathy construct.